My Brother's Keeper George McGovern and Progressive Christianity - Lempke, Mark A., 1983- (Book collections on Project MUSE., 2017)
"George McGovern is chiefly remembered for his landslide loss to Richard Nixon in 1972. Yet at the time, his candidacy raised eyebrows by invoking the prophetic tradition, an element of his legacy that is little studied. In My Brother's Keeper, Mark A. Lempke explores the influence of McGovern's evangelical childhood, Social Gospel worldview, and conscientious Methodism on a campaign that brought antiwar activism into the mainstream. McGovern's candidacy signified a passing of the torch within Christian social justice. He initially allied with the ecumenical movement and the mainline Protestant churches during a time when these institutions worked easily with liberal statesmen. But the senator also galvanized a dynamic movement of evangelicals rooted in the New Left, who would dominate subsequent progressive religious activism as the mainline entered a period of decline. My Brother's Keeper argues for the influential, and often unwitting, role McGovern played in fomenting a 'Religious Left' in 1970s America, a movement that continues to this day. It joins a growing body of scholarship that complicates the dominant narrative of that era's conservative Christianity"--Provided by publisher.